Coronary heart disease and stroke in the Sami and non-Sami populations in rural Northern and Mid Norway- the SAMINOR Study - Siri, Susanna Ragnhild; Eliassen, Bent Martin; Broderstad, Ann Ragnhild; Melhus, Marita; Michalsen, Vilde Lehne; Jacobsen, Bjarne K.; Burchill, Luke; Braaten, Tonje (Open Heart, 2020)
publishedVersion